The Panda-Derived Lactobacillus plantarum G201683 Alleviates the Inflammatory Response in DSS-Induced Panda Microbiota-Associated Mice - Zhou, Yi; Duan, Ling; Zeng, Yan; Niu, Lili; Pu, Yang; Jacobs, Jonathan P.; Chang, Candace; Wang, Jie; Khalique, Abdul; Pan, Kangcheng; Fang, Jing; Jing, Bo; et al. (Frontiers in Immunology, 2021)
Intestinal diseases are one of the main causes of captive giant panda death. Their special dietary habits and gastrointestinal tract structure often lead to intestinal epithelium damage and secondary intestinal infection. The captive giant panda is predisposed to suffer from microbiota dysbiosis due to long-term artificial feeding and antibiotic misuse. However, there are few reported probiotics to treat giant panda enteritis and the associated dysbiosis. This study aims to elucidate the mechanism by which Lactobacillus plantarum G201683 (L. plantarum G83), a promising panda-derived probiotic, exerts a protective effect on intestinal inflammation in the dextran sulfate sodium- (DSS) induced panda microbiota-associated (DPMA) mouse model. The DPMA mouse was generated by antibiotic treatment and 5% DSS drinking water administration to assess the effect of L. plantarum G83 on intestinal inflammation and microbiota in vivo. Our results demonstrated the successful generation of a DPMA mouse model with Enterobacteriaceae enrichment, consistent with the giant panda intestinal microbiota. L. plantarum G83 decreased clinical and histological severity of intestinal inflammation, enhanced intestinal tight junction protein expression (ZO-1, Occludin) and alleviated inflammatory cytokine production (TNF-) in the colon of DPMA mice. The administration of L. plantarum G83 altered microbiota composition by decreasing pathogen associated taxa including E. coli and increasing abundance of beneficial bacteria including Bifidobacterium spp. These changes in microbiota composition were associated with increased concentration of short chain fatty acids (SCFA), reduced NF-κB signaling, and altered balance of T helper cell subsets. Our findings support L. plantarum G83 as a promising probiotic to treat intestinal inflammation in the giant panda.